Of an Alien Homecoming : Reading Heidegger's Hölderlin. - Bambach, Charles R. (SUNY series in contemporary continental philosophy., 2022)
The first book-length study in English of the Heidegger-Hölderlin relation, addressing the tension between Heidegger's political commitments during National Socialism and Hölderlin's ideal of poetic dwelling.